Refiguring Lived Faith: A Hermeneutical Study of Catholic Migrants from East Nusa Tenggara in South Kalimantan - Antonius Bambang Doso Susanto; Raymundus I Made Sudhiarsa; Antonius Denny Firmanto (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This study examines the lived faith of Catholic migrants from East Nusa Tenggara (NTT) who have migrated to the Muslim-majority landscape of South Kalimantan, Indonesia. These migrants face a profound crisis of identity as they transition from a dominant religious environment to a marginalized minority status, necessitating a research objective that explores how their faith is reinterpreted amidst such socio-religious pressures. Employing a qualitative phenomenological-hermeneutical method, the research utilizes Paul Ricoeur’s threefold mimesis - prefiguration, configuration, and refiguration - as its primary interpretive framework. The findings reveal a significant narrative shift from an inherited “communal Catholic habitus” to a “refigured faith” characterized by personal agency and reflective commitment. This transformation is sustained through adaptive relational ethics, such as the sanctification of work and collaborative hospitality, which allow migrants to navigate their vulnerability. The study synthesizes these experiences to conclude that internal migration constitutes a vital locus theologicus, wherein the rupture of traditional religious structures does not erode faith but rather matures it into a more resilient, intentional, and relational existential orientation. Consequently, migration emerges as a transformative theological process that redefines the intersection of faith, culture, and minority existence in pluralistic societies.